Research progress on ultra-processed foods consumption and its association with health - Jiaqian ZHONG; Jiangyue YU; Zhengyuan WANG; Zhuo SUN; Jiajie ZANG (环境与职业医学)
With the rapid progress of industrialization and commercialization, the sales and population intake of ultra-processed foods (UPFs) are constantly increasing globally. High UPFs intake is associated with various health issues. This article provided a brief overview of various health outcomes and explored the possible causes for the health impacts of UPFs consumption from the perspectives of processing and production. The review found that high UPFs intake increased the risks of adult overweight/ obesity, type 2 diabetes, cancer mortality, and anxiety disorders; maternal preeclampsia, gestational hypertension, and gestational diabetes; childhood and adolescent overweight/ obesity. High UPFs intake also affected embryonic development and offspring language development. The possible explanations for the negative health outcomes associated with UPFs were as follows. The convenience and increased accessibility of UPFs affect the dietary structure of the population. The combined exposure to refined carbohydrates and fats added to UPFs increases the desire and motivation for more energy intake. The complex processing process leads to the loss of dietary fibers and micronutrients, affecting human satiety, digestion rate, chewing duration, and producing toxic compounds such as furan, heterocyclic amines, polycyclic aromatic hydrocarbons, and acrolein. The introduction of more types and higher doses of food additives and the migration of exogenous pollutants from packaging materials to food pose potential health and safety risks. At present, there is little research on the relationship between UPFs and human health in China. Based on the known health risks of UPFs, more in-depth research is needed in order to better understand the relationship between UPFs and human health.